The Material Well-being of Russians: Intergenerational Differentiation - V. N. Bobkov; E. V. Odintsova (Мир новой экономики)
The article is devoted to the problems of the material well-being of the Russian population. It presents the research results that continues the author's developments on the assessment of inequality in the distribution of the population by monetary income and housing provision. This study aimed to identify and analyse the inequality of material well-being in the aspect of intergenerational differentiation. The authors relied on the normative methodology for identifying material well-being based on the original system of social standards of monetary income and housing provision. The assessments based on data from the Russia Longitudinal Monitoring Survey (RLMS-HSE) (28th round, 2019). Data on the existing inequality in material well-being identified by social standards under three distribution models — one-criterion (monetary income, housing provision) and two-criterion (joint distribution according to the criteria of material well-being) — for three generations: youth, middle, and older generation. According to the results of the study, those who live in households with dependents (children, nonworking members of households) are the most vulnerable in terms of material well-being characteristics, and, on the contrary, those who live alone or from small households (2 people) are in the best position. At different “poles” of the material well-being are the young people living separately with children and the older generation — living alone or married couples. The results obtained in the course of the study can be used to increase the validity of social policy and develop targeted measures differentiated relative to different generations of Russians and their socio-demographic groups based on indicators of the actual distribution of material well-being — monetary income and/or housing provision.